2012
DOI: 10.1007/s13361-011-0332-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Protein Structural Resolution from Diethylpyrocarbonate-based Covalent Labeling and Mass Spectrometric Detection

Abstract: Covalent labeling and mass spectrometry are seeing increased used together as a way to obtain insight into the 3-dimensional structure of proteins and protein complexes. Several amino acid specific (e.g. diethylpyrocarbonate) and non-specific (e.g. hydroxyl radicals) labeling reagents are available for this purpose. Diethylpyrocarbonate (DEPC) is a promising labeling reagent because it can potentially probe up to 30% of the residues in the average protein and gives only one reaction product, thereby facilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 56 publications
1
65
0
Order By: Relevance
“…These modification conditions have been established by numerous previous studies of DEPC labeling of β2m by our group. 19,21-23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These modification conditions have been established by numerous previous studies of DEPC labeling of β2m by our group. 19,21-23 …”
Section: Methodsmentioning
confidence: 99%
“…DEPC provides good structural coverage as it can react with up to 30% of the residues in the average protein, providing an effective resolution around 8-10 Å. 23 While this level of structural detail can often help define protein‐protein interaction sites, this level of resolution may not be sufficient for identifying small molecule binding sites. Consequently, we are exploring the combination of information obtained from DEPC labeling with information from other labeling reagents.…”
mentioning
confidence: 99%
“…DS represents the variation in the extent of local disordering between transition state and the ground state. The decrease in the DS can be attributed to the oxidative modification of amino acid residues and initiation of crosslinking and aggregation which leads to the increase in enzymolysis activity [42]. DG had little change for ultrasonic treatment.…”
Section: Effects Of Single-frequency Countercurrent and Pulsed Ultrasmentioning
confidence: 99%
“…We have recently shown that diethylpyrocarbonate (DEPC) is a promising reagent molecule because of its ability to modify a wide range of amino acids [1, 10-14]. This potential to modify numerous amino acids enables DEPC to probe approximately 30% of the average protein [14]. Usually, proteins that are labeled with DEPC are then subjected to proteolysis so that the modification sites can be pinpointed to individual residues, thereby improving the resolution of this method.…”
Section: Introductionmentioning
confidence: 99%